2016
DOI: 10.1007/s10661-016-5393-1
|View full text |Cite
|
Sign up to set email alerts
|

Meteorology drives ambient air quality in a valley: a case of Sukinda chromite mine, one among the ten most polluted areas in the world

Abstract: The ambient air quality (AAQ) assessment was undertaken in Sukinda Valley, the chromite hub of India. The possible correlations of meteorological variables with different air quality parameters (PM10, PM2.5, SO2, NO2 and CO) were examined. Being the fourth most polluted area in the globe, Sukinda Valley has always been under attention of researchers, for hexavalent chromium contamination of water. The monitoring was carried out from December 2013 through May 2014 at six strategic locations in the residential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The role of atmospheric inversion especially subsidence and advective inversions (owing to the topography of the location) can't be ruled out. The role of temperature inversion in such higher concentrations of PM as localized events has been described by Mishra et al [1]. The lowest concentration of 29 µg/m 3 at A-3 location during September could be ascribed with higher wind speed facilitating horizontal dispersion of the particle in the atmosphere, which can take away the pollutant.…”
Section: Particulate Matter (Pm10 and Pm25)mentioning
confidence: 70%
See 1 more Smart Citation
“…The role of atmospheric inversion especially subsidence and advective inversions (owing to the topography of the location) can't be ruled out. The role of temperature inversion in such higher concentrations of PM as localized events has been described by Mishra et al [1]. The lowest concentration of 29 µg/m 3 at A-3 location during September could be ascribed with higher wind speed facilitating horizontal dispersion of the particle in the atmosphere, which can take away the pollutant.…”
Section: Particulate Matter (Pm10 and Pm25)mentioning
confidence: 70%
“…Air quality degradation is one of the inevitable impacts of developmental activities such as industrialization and urbanization leading to health implications on human and animals [1]. Both particulate matter (PM) and gaseous pollutants contribute to such degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Thousands of tons of waste are generated by the mines in the valley and thus spread to nearby water bodies and leach into the groundwater, contaminating local drinking water supplies. The contamination mainly occurs due to Cr(VI), which is considered a major environmental carcinogen and is highly toxic [36]. "In addition to the lack of sufficient space for disposing of waste, another major problem exists.…”
Section: Chromite Mining At Sukinda Valley Odishamentioning
confidence: 99%
“…In general, the synoptic patterns and anthropogenic emission densities were found to be the causes of air pollution episodes (Ji et al, 2012). Consequently, statistical studies using meteorological data and air pollution monitoring data have confirmed that meteorological conditions affect atmospheric pollution in numerous ways (Akyüz and Çabuk, 2009;Unal et al, 2011;Tian et al, 2014;Gong et al, 2015;Wang et al, 2015;Mishra et al, 2016).…”
Section: Introductionmentioning
confidence: 98%